PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI FINANSIAL TERHADAP KINERJA SALESMAN YANG DIMEDIASI OLEH ETOS KERJA - Pratama, Anugerah Putra; Sugiarto, Meilan; Soeprapto, Adi (Jurnal Ilmu Administrasi dan Bisnis, 2019)
Aim of this study is to analyze the impact of organizational culture and financial compensation on salesman performance mediated by work ethic. The sampling technique used in this study is simple random sampling and to analyze the impact between variabels used Partial Least Square (PLS-SEM). The results showed that organizational culture and financial compensation had a significant effect on the work ethic and salesman performance, both directly and indirectly. Several previous studies relating to organizational culture, compensation, employee performance, and work ethics were carried out separately not yet reviewed simultaneously in a model that was tested through empirical data with a path analysis approach using PLS-SEM as has been done by this research. Companies need to foster and unite fellow members in the team so that there is a compact, harmonious relationship and all work productively so that salesman performance can be maximized according to company expectations. Financial compensation provided by the company needs to properly consider aspects of the needs of its employees. Independence at work needs to be evaluated and improved so that every salesman can work without being dependent on others. Keywords : organizational behavior, financial compensation, work ethic, salesman performance.